1, 2, 3 to the zoo : a counting book - Carle, Eric. (New York : Putnam & Grosset Group, 1998)
Each car on the train has one more zoo animal than the one before, from the first car with an elephant to the last with ten birds.
"A PaperStar book"--P. facing t.p.
"Paperstar.".
Elem. School Library Collection.
School Library Journal.
School Library Media Quarterly (A.A.A.L.).
Booklist, September 2006.
Keywords: Counting -- Juvenile literature; Zoo animals -- Juvenile literature; Counting; Zoo animals; Counting; Zoo animals